Hubungan Pengetahuan Rekam Medis Elektronik (RME) dengan Kesiapan Perawat Menggunakan Rekam Medis Elektronik (RME) di Rumah Sakit Wonolangan Probolinggo - Mutmainah, Iin; Khotimah, Husnul; Sholehah, Baitus (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
According to the 2021 LAKIP (Performance Accountability Report of Government Agencies) data, 123 hospitals in Indonesia have integrated and implemented electronic medical records (EMR). In East Java, 13 hospitals have adopted EMR, but none in Probolinggo Regency have yet integrated this system. This study aims to examine the relationship between knowledge of Electronic Medical Records (EMR) and the readiness of nurses to use EMR at Wonolangan Hospital, Probolinggo. The study was conducted in 2023 with a population of 80 nurses, selected using the total sampling technique. The research employed a descriptive quantitative approach with statistical analysis using Spearman's rho correlation test, and data collection was done through questionnaires. The results indicated that in terms of knowledge, 70 nurses (87.5%) had good knowledge, 9 nurses (11.25%) had moderate knowledge, and 1 nurse (1.25%) had low knowledge. In terms of readiness, 51 nurses (63.75%) were categorized as having high readiness, 28 nurses (35%) as medium, and 1 nurse (1.25%) as low. The statistical test showed a P value of 0.000 (P < 0.05), indicating a significant relationship between knowledge of EMR and nurses' readiness to use EMR at Wonolangan Hospital, Probolinggo.